Charge transport and energy storage at the molecular scale: From nanoelectronics to electrochemical sensing - Bueno, Paulo R. [UNESP]; Davis, Jason J. (Royal Society of Chemistry (RSC), 2020)
This tutorial review considers how the fundamental quantized properties associated with charge transport and storage, particularly in molecular films, are linked in a manner that spans nanoscale electronics, electrochemistry, redox switching, and derived nanoscale sensing. Through this analysis, and by considering the basic principles of chemical reactivity, we show that 'dry' electronic and 'wet' electrochemical characteristics align within a generalized theoretical capacitative framework that connects charge conductance and electron transfer rate. Finally, we discuss the application of these joint theoretical concepts to key developments in nanosensors. This journal is